2020
DOI: 10.3390/ejihpe10040072
|View full text |Cite
|
Sign up to set email alerts
|

Is the Effect of Body Dissatisfaction on Depressive Symptoms Dependent on Weight Status? A Study with Early-to-Middle Adolescents

Abstract: Depression is a recognized mental health problem in adolescence and body dissatisfaction is an important risk factor. The main goal of this study is to examine the relationship between body dissatisfaction and depressive symptoms, and whether it depends on adolescents’ weight status, an issue that remains understudied. Two hundred and fourteen adolescents (12–16 years) completed self-report measures of depressive symptoms, body dissatisfaction and weight status (i.e., current body weight and height, to compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 78 publications
(128 reference statements)
1
11
0
Order By: Relevance
“…33 Taken together, future studies should aim to characterize the complex relationship among body image, depression, and body size, in order to develop strategies for treating weight misperceptions that are effective for youth with cooccurring overweight/obesity and depression. 7,53 Bullying and victimization is an additional factor identified as a potential mediator or moderator of the relationship between body size and depression in children and adolescents, including peer bullying victimization, perceived peer isolation, weight-related teasing, perceived parental teasing, and parental psychological control. 21,22,[33][34][35][36][37]54 One study reported that the weight-related victimization starts from childhood and becomes common in adolescents and young adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Taken together, future studies should aim to characterize the complex relationship among body image, depression, and body size, in order to develop strategies for treating weight misperceptions that are effective for youth with cooccurring overweight/obesity and depression. 7,53 Bullying and victimization is an additional factor identified as a potential mediator or moderator of the relationship between body size and depression in children and adolescents, including peer bullying victimization, perceived peer isolation, weight-related teasing, perceived parental teasing, and parental psychological control. 21,22,[33][34][35][36][37]54 One study reported that the weight-related victimization starts from childhood and becomes common in adolescents and young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies indicated that the relationship between BMI and depression is mediated by body image (e.g., perceived overweight and greater weight concern) in boys and girls. 7,21,22,[33][34][35][36][37] These studies consist of five cross-sectional studies and three longitudinal studies. Among them, two studies reported that the mediating effects of body dissatisfaction and pressure to be thin were only observed in girls but not in boys.…”
Section: Body Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Although the desire to lose weight arises from an early age, a greater number of preadolescent girls go to weight loss clinics, citing body dissatisfaction; the studies also indicate that age corresponds to the first stage of the transition toward adolescence, with important physical changes. Furthermore, they have already acquired the cultural norms and stereotypes underlying attractiveness [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In current societies, depressive symptoms seriously threaten adolescents’ mental health and socioemotional adjustment [ 1 ]. In this context, research about a diversity of risk factors and mechanisms for depression has been encouraged [ 1 , 2 , 3 , 4 ]. Therefore, this article focuses on the possible contribution of attachment and emotion awareness to depression in early to late adolescents.…”
Section: Introductionmentioning
confidence: 99%